Improving Electric Motor Learning Outcomes with Problem-Based Learning at SMKN 2 Ternate - Mustafa, Mustafa; Ibrahim, Rifandi; Seke, Fransiskus; Akhmad, Fandy (Department of Electrical Engineering Education, Faculty of Engineering, State University of Manado, 2022)
The background of this research is because the learning outcomes of Electric Motors at SMKN 2 Ternate are not maximized. The hypothesis is that if a problem-based learning method is applied, it can improve learning outcomes in electric motor lessons in class XI students of SMKN 2 Ternate. This study uses two research methods, namely quantitative and descriptive qualitative research. It collects data in this study through observation of test questions to determine learning outcomes. The test result data is in pre-test and post-test scores to determine student learning outcomes. This research includes classroom action research which is carried out to improve electric motor learning and increase student participation in learning. The results of observer observations that have been carried out on students from the first cycle to the second cycle are an increase in each cycle; namely, the average of the first cycle is 61.69. Then the results increased in the second cycle to 72.78, with 31 students in class XI TITL 2 SMKN 2 Ternate. That means classroom action research that uses problem-based learning methods on Electric Motor subjects in class XI TITL 2 can improve student learning outcomes.